PELANGGARAN KODE ETIK DAN PERILAKU HAKIM MAHKAMAH KONSTITUSI (STUDI KASUS PUTUSAN NOMOR 2/MKMK/L/11/2023) - Bim Ardono; Dilla Hariyanti (Fakultas Hukum Universitas Borobudur, 2025)
Violations of the code of ethics of judges that are rampant at the Constitutional Court level in Decision Number 90/PUU-XXI/2023 are violations of the code of ethics committed in the decision-making process. This study discusses violations of the code of ethics and behavior of Constitutional Court judges in Decision Number 2/MKMK/L/11/2023 and the imposition of sanctions by the Constitutional Court Honorary Council for violations of the code of ethics and behavior of constitutional judges in Decision Number 2/MKMK/L/11/2023 in accordance with applicable laws and regulations. The research method used is normative juridical. The results of the study explain that the Reported Party Anwar Usman has violated the code of ethics and behavior of Constitutional Court judges when examining and deciding case Number 90/PUU-XXI/2023 by referring to Constitutional Court Regulation Number 09/PMK/2006 concerning the Enforcement of the Declaration on the Code of Ethics and Behavior of Constitutional Judges. The Constitutional Court's Honorary Council issued a decision in accordance with applicable law with reference to Article 23 paragraph (2) letter h of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court in connection with Article 41 letter c of Constitutional Court Regulation Number 1 of 2023 concerning the Constitutional Court's Honorary Council which imposed sanctions on the Reported Party Anwar Usman in the form of dishonorable dismissal.